IMPLEMENTASI HUKUM DALAM MENANGGULANGI DELIK PROSTITUSI ONLINE MENGGUNAKAN PASAL 296 KUHP - Ferdinand De Lapasha; Ade Adhari (Jurnal Hukum Adigama, 2022)
The disparity in sentencing is something that naturally occurs in a decision. The generalunderstanding of disparity is that there is a wide range of dif erences in the sentencing of criminals incases of the same type or level of seriousness. Disparity is divided into two, namely disparity that canbe accounted for and also disparity that cannot be accounted for. There is no concrete definitionregarding the meaning of the disparity. To find and find out whether there are disparities in a decision,numerical punishment guidelines are needed using a consistency of outcomes approach. In thesentencing guidelines there are variables that have dif erent weights and will then be included in thesentencing table so that this is very helpful for judges in imposing criminal penalties. In writing thisthesis, the researcher uses 2 (two) decisions which are considered to have sentencing disparities. Theresearcher uses the decision No.Pid.Sus/2019/PN.Smn and the decision No.445/Pid.Sus/2020/PN.Pal.in the decision of the Sleman District Court, the defendant was sentenced to prison for 4 (four) months.Meanwhile, in the Palu District Court's decision, the defendant was sentenced to 2 years and 3 monthsin prison. It is clear that there is a disparity, but it cannot be judged whether this is a disparity that canbe accounted for or not. The 2 (two) decisions are also reviewed with the ITE Law and the CriminalCode.